The Effect of Risk and Service Quality on Customer Loyalty : (a Study of IAIN Kendari Students Using BSI Mobile Banking ) - Maguni, Wahyudin; Prayoga, Dimas (AGUSPATI Research Institute, 2025)
In mobile banking, customer loyalty is customer loyalty to continue using the mobile banking application for transactions. This research aims to see and test the influence of risk and service quality on customer loyalty of BSI Mobile Banking users among IAIN Kendari students. The data source used in this research is primary data in the form of a questionnaire. with a sample obtained of 100 IAIN Kendari student respondents who used mobile banking with a purposive sampling technique, using a questionnaire and processed using the Smart PLS 3.0 program. The tests used were validity test, reliability test, determinant efficiency test (R-Square) and also hypothesis testing. Based on the data analysis carried out, it was concluded that risk had a significant positive effect on customer loyalty, service quality had a significant positive effect on customer loyalty and risk and service quality simultaneously had a significant positive effect on customer loyalty of BSI Mobile Banking users.